Efektivitas Kewenangan Jaksa Pengacara Negara di Kejaksaan Negeri Lampung Timur dalam Penyelesaian Sengketa Perdata Nonlitigasi - Yeni Puspitasari; Choirul Salim (Al-Mizan (e-Journal), 2026)
The authority of the State Attorney (Jaksa Pengacara Negara/JPN) in resolving civil disputes through non-litigation mechanisms is part of the Attorney General’s Office function in the field of Civil and State Administrative Law from the perspective of Administrative Law. This authority is based on Article 30, paragraph (2) of Law Number 11 of 2021, which provides the legal basis for the Prosecutor’s Office to represent the state or government, both inside and outside the court, through a layered basis of institutional attribution, delegation via a Special Power of Attorney, and individual assignment. In practice at the Lampung Timur District Prosecutor’s Office, the implementation of non-litigation authority through an eight-stage procedure, from application to negotiation, mediation, and settlement, has not been optimal due to low compliance by disputing parties and the absence of enforceable authority over settlement agreements. This study aims to analyze the basis and implementation of the JPN authority, measure its effectiveness in handling BPJS Kesehatan default cases, and identify the juridical and non-juridical factors that affect it. The novelty of this research lies in its empirical analysis of JPN’s non-litigation authority by integrating juridical and non-juridical factors that influence the low success rate of dispute resolution, particularly in BPJS Kesehatan default cases at the Lampung Timur District Prosecutor’s Office. This research employs the theory of authority and the theory of legal effectiveness using an empirical juridical method with statutory and field approaches. Primary data were obtained through interviews with State Attorneys, while secondary data were collected from legislation, literature, academic journals, and official prosecutorial documents. The findings show that of 119 non-litigation cases handled in 2025, only 26.9 percent were successfully resolved, as settlement agreements still lack binding executorial force and are further hindered by non-juridical factors such as low attendance, limited coordination, and the financial capacity of the disputing parties; the study accordingly proposes strengthening the legal status of settlement agreements and institutional capacity to improve future effectiveness.